THE EFFECTIVENESS OF ICE AGE 3 CARTOON CLIP IN SPEAKING AT PPLG ELEVENTH GRADE OF SMK N 3 METRO - Oktipia, Rizki Nurlidia; Qomar, Aulia Hanifah; Refai, Refai (PHILOLOGY Journal of English Language and Literature, 2025)
Speaking is necessary for students to communicate with others. It is necessary to master the speaking skill by bringing English learning experiences into practice. This research aims to find out whether the ice age 3 cartoons is effective and significantly for PPLG eleventh grade students’ speaking skill at SMK N 3 Metro. This research used Quasi-Experimental Design. The sample of this research is class XI PPLG-A as the experimental class and class PPLG-B as the control class using the Random Sampling method. PPLG-A consists of 32 students as an experimental class and PPLG-B consists of 32 students as a control class. The results of the Wilcoxon Matched Pairs test in first hypothesis, the sig value is 0.000 which is less than 0.05 (0.000 <0.05). Ha is accepted. There is an effect of ice age 3 cartoon to support the students of PPLG eleventh grade speaking skill at SMK N 3 Metro. The Mann-Whitney U-Test in second hypothesis test, the sig value is 0.000, which is less than 0.05 (0.00 <0.05). Ha is accepted. There is significance of ice age 3 cartoon to support the students of PPLG eleventh grade speaking ability at SMK N 3 Metro. This research concluded that the Ice Age 3 cartoon clip has been proven to be an effective and significant method to improve speaking skills among eleventh grade PPLG students at SMK N 3 Metro. Future researchers should examine the long-term effects of multimedia devices on language acquisition to better understand their lasting impact on students’ speaking skills.